Morphological characteristics of elite female volleyball players under 19 - Joksimovic, M.; Goranovic, K.; Petkovic, J.; Badau, D.; Hantanu, C. G. (International Journal of Morphology, 2023)
The aim of the article is to determine the differences in morphological characteristics and jumping abilities between female volleyball players who play for different national teams. The sample consists of 48 elite female volleyball players from four different national teams which participated in European championship qualifications. The variables studied were: body height, mass, body mass index, standing reach and spike reach. The results show differences in body mass index, standing reach and spike reach. These differences are related to the needs of the different positions with regard to the actions they execute. In conclusion morphological parameters are important components of performance in many sports (volleyball). Different sports disciplines require different body parameters and body structure for maximum performance.